Molecular, rheological and physicochemical characterisation of puka gum, an arabinogalactan-protein extracted from the Meryta sinclairii tree. (15th September 2019) - Wee, May S.M.; Sims, Ian M.; Goh, Kelvin K.T.; Matia-Merino, Lara
Graphical abstract: Highlights: Puka gum has a molecular weight of 5.91 × 10 6 Da and RMS radius of 55.9 nm. Branched, compact spherical conformation with solubility up to 25% w/w. Low zero-shear viscosities and exhibits mainly Newtonian to shear-thinning. behaviour. Anionic polysaccharide which is sensitive to ionic strength and pH. Overall molecularly similar to gum arabic but with molecular weight 10 times larger. Abstract: A water-soluble polysaccharide (type II arabinogalactan-protein) extracted from the gum exudate of the native New Zealand puka tree ( Meryta sinclairii ), was characterised for its molecular, rheological and physicochemical properties. In 0.1 M NaCl, the weight average molecular weight (Mw ) of puka gum is 5.9 × 10 6 Da with an RMS radius of 56 nm and z-average hydrodynamic radius of 79 nm. The intrinsic viscosity of the polysaccharide is 57 ml/g with a coil overlap concentration 15% w/w. Together, the shape factor, p, of 0.70 (exponent of RMS radius vs. hydrodynamic radius), Smidsrød-Haug's stiffness parameter B of 0.031 and Mark-Houwink exponent α of 0.375 indicate that the polysaccharide adopts a spherical conformation in solution, similar to gum arabic. The pKa is 1.8. The polysaccharide exhibits a Newtonian to shear-thinning behaviour from 0.2 to 25% w/w. Viscosity of the polysaccharide (1 s −1 ) decreases with decreasing concentration, increasing temperature, ionic strength, and at acidic pH.